1972
DOI: 10.1080/00139307209435449
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Pesticide by Humic Substances. A Review

Abstract: The l i t e r a t u r e p e r t a i n i n g t o adsorption o f p e s t i c i d e by humic substances has been reviewed, R e s u l t s o f various i n v e s t ig a t i o n s and mechanisms f o r p e s t i c i d e a d s o r p t i o n a r e discussed, The e f f e c t s o f such f a c t o r s as temperature and pH, and t h e techniques f o r t h e s t u d y o f p e s t i c i d e a d s o r p t i o n by humic substances a r e o u t l i n e d . 11. INTRODUCTION Humic substances a r e . t h e p r i n c i p a l organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

1973
1973
2010
2010

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 18 publications
0
7
0
3
Order By: Relevance
“…cides by humic substances (Hayes 1970; The importance of humic substances in in- Khan 1972;Stevenson 1972)' These include fluencing the activity, behavior, bio-avail-ion exchange' hydrogen bonding, protonaability ind OegraOaUitity of herbicides in tion, charge transfer, ligand exchange, cosoils has been documented in recent reviews ordination through a metal ion, van der by Hayes (1970), Khan ( 1972), and Steven-Waals forces, and hydrophobic bonding' son (1972). Numerous reports have ap-Despite the considerable amount of repeared in the literature during the past dei-search undertaken, very little attention has ade indicating that humic substances, which been paid to the-equilibrium and kinetic represent the most active fraction of organic aspect of the problem.…”
Section: Introductionmentioning
confidence: 99%
“…cides by humic substances (Hayes 1970; The importance of humic substances in in- Khan 1972;Stevenson 1972)' These include fluencing the activity, behavior, bio-avail-ion exchange' hydrogen bonding, protonaability ind OegraOaUitity of herbicides in tion, charge transfer, ligand exchange, cosoils has been documented in recent reviews ordination through a metal ion, van der by Hayes (1970), Khan ( 1972), and Steven-Waals forces, and hydrophobic bonding' son (1972). Numerous reports have ap-Despite the considerable amount of repeared in the literature during the past dei-search undertaken, very little attention has ade indicating that humic substances, which been paid to the-equilibrium and kinetic represent the most active fraction of organic aspect of the problem.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Humic substances (HS) such as humic acids (HAs), fulvic acids (FAs) and humin are particularly of interest to pesticide sorption studies because these fractions are more chemically reactive with pesticides than nonhumified substances. [5,6] HS can be fractionated by sequential extractions with sodium hydroxide (NaOH) followed by sodium pyrophosphate (Na 4 P 2 O 7 ). [7] HAs and FAs extracted by NaOH represent the fractions present as free form C. [7] HAs and FAs that are not extractable by NaOH but can be extracted by Na 4 P 2 O 7 are considered to be the combined form C fractions [7] and in closer contact with clay minerals than free form C. [8,9] Piccolo et al [10] demonstrated that NaOH-extracted HS have a greater sorption capacity for atrazine (a weakly-basic herbicide) than Na 4 P 2 O 7 -extracted HS.…”
Section: Introductionmentioning
confidence: 99%
“…Ces composés étant peu solubles dans les eaux, les risques de pollution par ruissellement ou drainage sont donc limités. Leurs associations avec les substances humiques (Khan, 1972) peut cependant modifier leur activité entraînant notamment une augmentation de leur solubilité et donc de la pollution des eaux (WERSHAW et ai, 1969 ;CHIOU et al, 1986 ;CHIOU et al, 1987 ;AYELE et al, 1989 ;FABRE étal., 1990).…”
Section: Introductionunclassified